Training and Mentoring for Strengthen Brand Identity for MSMEs/WUBs Koperasi Bunda Sejahtera - Suharyati ,; Kery Utami; Dea Delia Lestari (PT Inovasi Pratama Internasional, 2026)
Strengthening brand identity is a key strategy to enhance SME competitiveness, particularly for New Entrepreneurs (WUB) at the early stages of business development. This community service activity aims to improve the knowledge and skills of WUB members of the Bunda Sejahtera Cooperative, Depok, in creating innovative products, designing effective and informative labeling, and developing market-oriented packaging. The implementation method included interactive lectures, discussions, and hands-on practice in producing a “Café-style Herbal Drink” based on traditional herbs, complemented with modern label and packaging design training. Twenty participants joined the program, dominated by the culinary sector (50%), with capital under Rp 10 million (55%), monthly turnover below Rp 5 million (75%), and social media use limited mainly to WhatsApp (100%). Evaluation was conducted through validity and reliability tests of the questionnaire (SPSS 23) and frequency distribution analysis. All indicators were valid (r > 0.444; p < 0.05) and reliable (Cronbach’s Alpha 0.709–0.797). The average understanding level reached 85%, categorized as “Highly Understand” for Brand Identity, Innovative Products, and Packaging (86%), and “Understand” for Labeling (80%). Practical implementation of innovative product creation reached 86%, surpassing the 65% target. The program resulted in improved knowledge, skills, product health quality, and potential income for partners. This initiative aligns with SDGs 1, 3, 8, 9, 12, and 17, and supports higher education KPI 5. The results show that training integrating theory and practice effectively enhances SME/WUB branding capacity sustainably.